MITOS KECANTIKAN PEREMPUAN EKSTRA MELALUI IKLAN NIVEA “EXTRA CARE FOR EXTRA WOMEN” (Jurnal Kajian Media, 2021)
Beautiful woman standards cannot be separated from the media construction of the meaning of beauty. The media displays the standard of beauty that is consumed every day by the people of Indonesia through content and also advertising. An advertisement cannot be separated from a visual character that is built in such a way that it can be an inspiration or can represent the product or service advertised, not only that the visual character in the ad also shows other aspects such as social values and norms, images and lifestyle. This aspects standard certainly affects the views of Indonesian women on beauty. Nivea realizes that every woman is beautiful and has their own potential, so Nivea creates an Nivea extra care for extra women ad. This study aims to determine the myth of extra female beauty from the Nivea Extra Care for Extra Women ad. His research methods are qualitative, Roland Barthes's semiotics and Oswald's semiotic marketing, related to beauty myths. The object is the Nivea Extra Care for Extra Women ad on Youtube. Keywords: Beauty Mthy, Semiotic Marketing, Barthes, Advertisement